Narrative Now The art of telling stories in dance - Simpson, Jane (Dance Books Ltd., Alton,Hampshire (UK), 2006)
The art of telling stories in dance. PALABRAS CLAVE: Royal Ballet, narrative ballet, The Rake's Progress, opera, Ninette De Valois.